Percepções sobre o nível de maturidade em gestão estratégica na secretaria municipal das finanças de Fortaleza - Souza, Chayanne Matos de (2023)
The implementation of a strategic management model in public entities is relatively new, especially in Brazil, and this is a reflection of the administrative reforms that happened in the country at the end of the 20th century. The managerial perspectives of the so-called new public management and a public administration focused on citizen participation, proposing more flexible and efficient public services, with more quality and targeting the citizen. In 2017, the Municipal Secretariat of Finance (Sefin) implemented a strategic management model, using theoretical foundations and tools based on the Balanced Scorecard (BSC). In 2022, it continued to advance in its strategic management, with the insertion of the method based on Objectives and Key Results (OKR). As a result, there is a need to assess the level of maturity in strategic management that Sefin is currently at. In this sense, this study aims to evaluate the perception of Sefin's staff regarding the level of maturity in strategic management, in order to identify the perception of the staff in the dimensions of maturity in strategic management; analyze the perception of the main difficulties and improvement solutions for the respective dimensions; and raise proposals on new dimensions or aspects that should be considered in the assessment of maturity in strategic management. To achieve the objective, it was necessary to verify the level of maturity, using the Strategic Management Maturity Model™, created by the Balanced Scorecard Institute, as well as adapting the study by Silva (2017). This work uses bibliographical, documentary and field research, carried out through a single case study, at Sefin. This is a mixed study, with qualitative and quantitative approaches. As a support tool for carrying out the research, a questionnaire was applied and an interview was conducted. Reliability analyses, descriptive and inferential statistics were performed. For the analysis of the results, triangulation was carried out, in order to verify convergent and divergent points in the research findings. The results obtained met the objectives of the research, with the maturity levels Managed and Focused being raised, in the view of the expanded public, in the view of a smaller public, which works directly with the strategy, and the perception was at a Structured and Proactive level. The difficulties were raised and categorized. Improvement proposals were structured and pointed out in the study. Finally, new categories were suggested to complement the theoretical model used, such as, for example, analyzing people's happiness at work, aligned with strategic management, among several interesting aspects of study and analysis.